THE EFFECT OF SUSTAINABLE MARKETING ACTIVITIES, CUSTOMER TRUST, CUSTOMER SATISFACTION, PRODUCT QUALITY, PRICE ON CUSTOMER LOYALTY MEDIATED BY BRAND IMAGE (RESEARCH ON UMKM IN BATAM CITY) - Fasha, Andina; Louis, Celwin; Gitty Ramadani, Arienda (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
This study examines the impact of sustainable marketing activities. Customer trust, satisfaction, product quality and price-to-customer loyalty among MSMEs in Batam, with data collected from 311 respondents representing various demographic groups. Using a purposive sampling technique with brand image as the central variable. The research uses a quantitative analytical approach through structural equation modeling (SEM) using Smart-PLS. The main findings reveal a significant positive impact of sustainable marketing activities. Customer trust and satisfaction with brand image while brand image significantly increases customer loyalty. Product quality shows a direct positive impact on loyalty. Meanwhile, price does not significantly affect loyalty. The study concludes that developing sustainable marketing and promoting a strong brand image are important strategies for MSMEs to build long-term customer loyalty.